2005
DOI: 10.1093/geront/45.6.820
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Undiagnosed Geriatric Health Conditions Among Adult Protective Service Clients

Abstract: This new effort to link APS workers with geriatric clinicians conducting in-home health assessments proved effective for identifying a high prevalence of remediable health conditions among APS clients suffering various manifestations of elder mistreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Findings were demonstrated that high percent of caregivers were afflicted by mild and moderate depression. Cameron and Beach also reported same results [18,19]. Depression, even in mild level, disturbs the mental health.…”
Section: Discussionsupporting
confidence: 54%
“…Findings were demonstrated that high percent of caregivers were afflicted by mild and moderate depression. Cameron and Beach also reported same results [18,19]. Depression, even in mild level, disturbs the mental health.…”
Section: Discussionsupporting
confidence: 54%
“…This echoed with the recent study of the population study by Dong and Simon 2010, which showed that impairment in physical function was not independently associated with increased elder abuse. As in other literature findings, we identified multiple factors contributing to caregiver stress, which created negative impact on caregivers' health, their financial status and well-being (Heath et al, 2005;Hoffman and Mendez-Luck, 2011;Mackenzie and Greenwood, 2012). In our study we recognized several factors, which appeared to work together in facilitating desirable outcomes of caregiving and thus preventing elder abuse.…”
Section: Caregiver Stress Is Not the Only Explanation For Elder Abusesupporting
confidence: 68%
“…Research showed that caregiver stress was not the only explanation for elder abuse. The attitude of caregivers towards caring activities, pre-morbid relationship with care-recipients, and demands of care were equally important in contributing to caregiver stress (Anetzberger, 1987;Compton et al, 1997;Heath et al, 2005;Pillemer and Suitor, 1992). Since 2002, a study by the National Center of Elder Abuse has attributed caregiver stress to burden, but previous studies had failed to account for the fact that some caregivers with heavy demands experienced little stress, while other caregivers with fewer demands experienced high levels of stress.…”
Section: Caregiver Stress and Elder Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, validly completed TRIOs should reflect significant and substantial differences in the prevalence of individual risk, intervention, and outcome indicators anticipated to be strongly associated with a specific form of abuse or neglect. Conversely, we should not find substantial differences between the two groups in the prevalence of TRIO items related to more universal risk factors such as cognitive decline and depression (Bomba, 2006; Heath, Brown, Kobylarz, & Castaño, 2005) and the receipt of more generalized APS interventions such as education/information sharing and building a positive social relationship between the APS worker and the client.…”
Section: Methodsmentioning
confidence: 81%